2020
DOI: 10.1016/j.heliyon.2020.e03482
|View full text |Cite
|
Sign up to set email alerts
|

Non periodic oscillations, bistability, coexistence of chaos and hyperchaos in the simplest resistorless Op-Amp based Colpitts oscillator

Abstract: In the framework of a project on simple circuits with unexpected high degrees of freedom, we report an autonomous microwave oscillator made of a CLC linear resonator of Colpitts type and a single general purpose operational amplifier (Op-Amp). The resonator is in a parallel coupling with the Op-Amp to build the necessary feedback loop of the oscillator. Unlike the general topology of Op-Amp-based oscillators found in the literature including almost always the presence of a negative resistance to justify the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The architecture of the proposed VCO is based on the Colpitts structure studied in the references [16][17][18] and the structure proposed by the authors in [12] as shown in Figure 2. The active part of this oscillator consists of two transistors pHEMT 1 and pHEMT 2: each one has 4 fingers and a gate length and width of 0.25 µm and 20 µm, respectively.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%
“…The architecture of the proposed VCO is based on the Colpitts structure studied in the references [16][17][18] and the structure proposed by the authors in [12] as shown in Figure 2. The active part of this oscillator consists of two transistors pHEMT 1 and pHEMT 2: each one has 4 fingers and a gate length and width of 0.25 µm and 20 µm, respectively.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%
“…These authors used an electronic circuit of a few components Tchitnga [23] out of a family of simple chaotic circuits comprising a coil Tchitnga Talla & Zebaze Nanfa'a [24][25][26] to generate electromagnetic signals of various periods (period-1, period-2, period-4) as well as a chaotic signal. These various signals were applied to the bean plants during their evolution 24 hours a day and 7 days a week.…”
Section: Krylov and Tarakonovamentioning
confidence: 99%
“…Simpler analog chaos oscillators can replace digital chaotic communication for resourceconstrained IoT sensors and nodes. Various chaotic oscillators, including Colpitts [36], have been extensively studied [37][38][39][40][41]. Colpitts chaos oscillators, in particular, have garnered attention for their simple schematic.…”
Section: Introductionmentioning
confidence: 99%